Gaps in Alcohol Screening and Intervention Practices in Surgical Healthcare: A Qualitative Study. Issue 2 (March 2021) - Fernandez, Anne C.; Guetterman, Timothy C.; Borsari, Brian; Mello, Michael J.; Mellinger, Jessica; Tonnesen, Hanne; Hosanagar, Avinash; Morris, Arden M.; Blow, Frederic C.
Abstract : Objectives: Risky alcohol use before surgery is associated with an increased risk of postoperative complications and longer hospital stays. Preoperative alcohol interventions can improve surgical outcomes but are not commonly integrated into routine care. This study sought to better understand patient's and provider's perceptions of alcohol-related surgical health and healthcare practices and illuminate gaps in care and how they could be improved. Methods: This study used a descriptive qualitative research design. Data were collected between July 2017 and March 2018. One-on-one interviews assessed domains related to knowledge, gaps in alcohol-related screening and intervention, and interest in enhancing alcohol-related care. Key themes emerged from a process of iterative coding and thematic analysis. Results: Participants included elective surgical patients who met alcohol screening criteria (n = 20) and surgical healthcare providers (n = 9). Participants had modest or low awareness of alcohol-related surgical health risks. Basic alcohol screening was a routine part of care, but results were often discounted or overlooked. Providers did not routinely initiate preoperative alcohol education or intervention. Providers viewed improving alcohol-related clinical practices as a low priority. Patients were interested in receiving alcohol interventions before surgery if they were delivered in a nonjudgement style and focused on surgical health optimization. Conclusions: This study highlights potential gaps in alcohol-related knowledge and care, and found providers place a low priority on alcohol interventions in the perioperative context. Given the high complication rate associated with preoperative alcohol use, these topics are worthy of future research. To be successful strategies to overcome specific barriers to alcohol screening and intervention must address the needs of patients and providers. Abstract : Supplemental Digital Content is available in the text